Dyssynchrony and perinatal psychopathology impact of child disease on parents-child interactions, the paradigm of Prader Willi syndrom. Issue 4 (November 2016) - Viaux-Savelon, Sylvie; Rosenblum, Ouriel; Guedeney, Antoine; Diene, Gwenaelle; Çabal-Berthoumieu, Sophie; Fichaux-Bourin, Pascale; Molinas, Catherine; Faye, Sandy; Valette, Marion; Bascoul, Céline; Cohen, David; Tauber, Maïthé
Highlights: Rhythms between a baby and his/her depressed mother. Emotional availability and a mutual comprehension between the partners in the context of a dyadic affective system. Emergence of our perception of non-acted motor behaviors. Abstract: Background: Infant-mother interaction is a set of bidirectional processes, where the baby is not only affected by the influences of his caregiver, but is also at the origin of considerable modifications. The recent discovery of biological correlates of synchrony during interaction validated its crucial value during child development. Here, we focus on the paradigmatic case of Prader-Willi Syndrome (PWS) where early endocrinal dysfunction is associated with severe hypotonia and early feeding disorder. As a consequence, parent-infant interaction is impaired. In a recent study (Tauber et al., 2017), OXT intranasal infusion was able to partially reverse the feeding phenotype, infant's behavior and brain connectivity. This article details the interaction profile found during feeding in these dyads and their improvement after OXT treatment. Methods: Eighteen infants (≤6 months) with PWS were recruited and hospitalized 9 days in a French reference center for PWS where they were treated with a short course of intranasal OXT. Social withdrawal behavior and mother-infant interaction were assessed on videos of feeding before and after treatment using the Alarm Distress Baby (ADBB) Scale and the Coding Interactive Behavior (CIB) Scale. Raters were blind to treatment status. Results: At baseline, infants with PWS showed hypotonia, low expressiveness of affects, fatigability and poor involvement in the relationship with severe withdrawal. Parents tended to adapt to their child difficulties, but the interaction was perturbed, tense, restricted and frequently intrusive with a forcing component during the feeding situation. After OXT treatment, infants were more alert, less fatigable, more expressive, and had less social withdrawal. They initiated mutual activities and were more engaged in relationships through gaze, behavior, and vocalizations. They had a better global tonicity with better handling. These modifications helped the parents to be more sensitive and the synchrony of the dyad was in a positive transactional spiral. Conclusion: Dys-synchrony can be induced by children's pathology as well as parental pathology with emotional and developmental impact in the both cases. The PWS paradigm shows us the necessity to sustain early parents-child relationship to avoid establishment of a negative transactional pattern of interaction that can impact child's development.